Treatment of pediatric, adolescent, and young adult patients with fusion-positive Alveolar Rhabdomyosarcoma infiltrating regional lymph nodes in the European CWS-2002P and RMS 2005 studies and the soft tissue sarcoma registry - Heinz, Amadeus Tilman; Ciuffolotti, Melissa; Merks, Johannes H. M.; Schönstein, Anton; Minard-Colin, Véronique; Fuchs, Jörg; Guillen, Gabriela; Timmermann, Beate; Vokuhl, Christian; Koscielniak, Ewa; Chisholm, Julia C.; Sparber-Sauer, Monika; et al. (Pediatric blood & cancer, 2025)
Background Patients with alveolar rhabdomyosarcoma (ARMS) with regional lymph node involvement (N1) are defined as “very-high-risk rhabdomyosarcoma” in Europe. Different chemotherapy regimens were used in European study protocols. Methods Patients with FOXO1 fusion-positive N1 ARMS registered in the CWS-2002P study, the EpSSG RMS 2005 study, and SoTiSaR were retrospectively investigated. Patients received systemic treatment with chemotherapy (CHT) and local treatment of primary tumor (PT) and involved lymph nodes (LN) with radiotherapy (RT) and/or surgery. Kaplan-Meier estimators and Cox regression were used to examine event-free survival (EFS) and overall survival (OS) according to prognostic factors and treatment. Results A total of 156 patients registered in RMS 2005 (n = 99), CWS-2002P (n = 20), and SoTiSaR (n = 37) between 2003 and 2020 were eligible for this analysis. Median age at diagnosis was 10.2 years [0.1-21.9]. Treatment comprised CHT with IVADo (ifosfamide, vincristine, actinomycin-D, doxorubicin, n = 93; 60%), VAIA (vincristine, actinomycin-D, ifosfamide, adriamycin/doxorubicin, n = 53; 34%) or other regimens (n = 10; 6%); resection of the PT (n = 89; 57%), LN sampling or dissection (n = 92; 59%), and/or RT (n = 139; 89%). Maintenance treatment (MT) was added in n = 99/135 (73%) patients who achieved complete remission. Five-year EFS and OS of the cohort were 45% and 47%, respectively. Age and tumor size were independent prognostic factors for EFS. Local treatment applied to the LN with surgery, RT or both significantly improved EFS (p = 0.02) and OS (p = 0.04), with no difference between the modalities (p = 0.7). Conclusions Patients with fusion-positive N1 ARMS carry a poor prognosis. Adequate local treatment of LN improved survival.